Implementation of the Guided Discovery Learning Model Using Web-Based Learning Media to Improve Vocational School Students' Cognition - Jasmine Tsania; Budi Laksono Putro; Eki Nugraha (Universitas Pendidikan Indonesia, 2023)
Database subjects are considered difficult to understand because they are abstract and require students to learn, master, and understand the concepts of the subjects being taught. This study aims to understand how the application of the guided discovery learning model using web-based learning media can improve the cognitive abilities of vocational students. The research method used is the Smart Learning Environment Establishment Guideline (SLEEG) and the pre-experimental research design type is one group pretest-posttest. The research subjects used were students of class XI RPL 1 at SMK Bina Wisata Lembang. The results obtained from this study through the calculation of the gain test resulted in an average gain of 0.50 and included the 'medium' effectiveness criteria. Students respond to learning media with a percentage value of 85% where this number is included in the 'very good' category. So, the end of this study concluded that web-based learning media with the Guided Discovery Learning model can improve the cognitive skills of vocational students in database subjects.